A Concrete Pouring Temperature Forecast Method for Hydraulic Structures. Issue 1 (January 2020) - Zhu, Zhenyang; Liu, Yi; Tan, Yaosheng; Zhou, Mengxia
Abstract: To address problems with the existing concrete pouring temperature forecast methods, an improved forecast method is presented in this paper. A concrete temperature variation calculation method during pouring is proposed. In this method, the effect of the external environmental temperature on the concrete pouring temperature for various measures is calculated using a finite element model. The relationships between heat conductivity, thermal diffusivity, surface heat transfer coefficient and the concrete temperature rise coefficient are obtained via fitting, and the reliability of these relationship equations are verified.